2014
DOI: 10.2146/ajhp130597
|View full text |Cite
|
Sign up to set email alerts
|

Medication absorption considerations in patients with postpyloric enteral feeding tubes

Abstract: The implications of absorption site should be considered for all patients receiving medications via postpyloric feeding tubes. Several medications cannot be administered through alternative routes because gastric acid is needed for their absorption, the medications may bind to the tubing, or drug absorption is altered at the intestinal site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 66 publications
0
31
0
3
Order By: Relevance
“…54 Feeding tubes can deliver enteral nutrition and orally administered medications directly to the stomach, duodenum, or jejunum.…”
Section: Concern 7: My Patient Has a Feeding Tubementioning
confidence: 99%
“…54 Feeding tubes can deliver enteral nutrition and orally administered medications directly to the stomach, duodenum, or jejunum.…”
Section: Concern 7: My Patient Has a Feeding Tubementioning
confidence: 99%
“…Before administering drugs into small bowel, the following elements should be considered: absorption site and potential local adverse effects, potential reaction with the feeding tube (blockade), need for gastric acid to be absorbed, and liquid form and not tablets/capsules [79]. These elements should be included in the drug information.…”
Section: Administration Of Medicinesmentioning
confidence: 99%
“…These elements should be included in the drug information. However, a recent paper found that despite its potential clinical significance, this information is not given [79].…”
Section: Administration Of Medicinesmentioning
confidence: 99%
See 2 more Smart Citations